The effect of processing conditions on the dielectric properties of doped calcium lanthanum nickelate - Yulia A. Deeva; Abdullo A. Mirzorakhimov; Alexey Yu. Suntsov; Nadezhda I. Kadyrova; Nina V. Melnikova; Tatyana I. Chupakhina (Chimica Techno Acta)
The influence of thermal and thermobaric (TBT) effects on the structure, microstructure, and dielectric properties of ceramics based on solid solutions of the La1.8Ca0.2Ni0.8M0.2O4+δ (M = Co, Cu) composition was studied. TBT treatment of the samples leads to a change in the grain morphology of ceramics and an increase in the dielectric constant compared to its value only after heat treatment. The change in the anisotropy of the coordination (La,Ca)O9 and (Ni,M)O6 polyhedra after TBT contributed to interlayer polarization in the crystal structure of La1.8Ca0.2Ni0.8M0.2O4+δ.